Health problems associated with irritable bowel syndrome: analysis of a primary care registry. Issue 10 (24th March 2018) - Clevers, E.; Vaes, B.; Henrard, S.; Goderis, G.; Tack, J.; Törnblom, H.; Simrén, M.; Van Oudenhove, L.
Summary: Background: Associations between irritable bowel syndrome and other health problems have been described, but comprehensive reports are missing, especially in primary care. Aims: To investigate which health problems are associated with irritable bowel syndrome, how they cluster together and when they are typically diagnosed relative to irritable bowel syndrome. Methods: We used Intego, a general practice registry in Flanders, Belgium. Patients with an irritable bowel syndrome diagnosis (n = 13 701) were matched with controls without gastrointestinal diagnosis and controls with organic gastrointestinal disease. Long‐term prevalences of 680 symptoms and diagnoses were compared between patients and controls. Results were summarised using functional enrichment analysis and visualised in a network and we calculated incidence rate ratios in the 10 years before and after the irritable bowel syndrome diagnosis for the network's key components. Results: Various symptoms and infections, but not neoplasms, were enriched in irritable bowel syndrome patients compared to both control groups. We characterised the comorbidities of irritable bowel syndrome as psychosocial health problems, urogenital symptoms and infections, musculoskeletal symptoms and other somatic symptoms. These had a uniform incidence in the years around the irritable bowel syndrome diagnosis, and did not structurally precede or follow irritable bowel syndrome. Conclusions: Irritable bowel syndrome shares long‐term associations with psychosocial health problems, urogenital symptoms and infections, musculoskeletal symptoms and other somatic symptoms in primary care. Clinicians are encouraged to take comorbidities into account when diagnosing and managing irritable bowel syndrome, as this may have important treatment implications. Abstract : Linked Content This article is linked to Whorwell paper. To view this article visithttps://doi.org/10.1111/apt.14659 .